Getting back to the event : COVID-19, attendance and perceived importance of protective measures - Perić, Marko, ekonomist (Array, 2021)
Current COVID-19 realities impose additional challenges to sporting event organisers who now have to consider and include new protective measures for the safety and security of both active and passive participants. This study focuses on event consumers and issues related to their intention to attend future sporting events and their perception of how important they find some of the safety-related protective measures when attending sporting events following the COVID-19 crisis. Based on the empirical study of residents from one Middle East and two European countries, the results suggest that, once all restrictions on movement and sporting event attendance is allowed to resume, most of the respondents will attend events in their home country within few weeks. In addition, the respondents from a country that experienced more severe consequences of the pandemic perceive all protective measures as more important than respondents from countries that were less affected.